Improvement of the performance of solar channels by using vortex generators and hydrogen fluid - Menni, Younes; Ameur, Houari; İnç, Mustafa (Springer, 2022)
An attempt is made to enhance the thermal hydrodynamic performance of a solar channel by using vortex generators including attached fins and detached bars. Hydrogen gas is used as a working fluid under turbulent flow conditions. The computational fluid dynamics method is used to achieve the investigations. Governing equations among fluid and solid sections are determined and solved by the computational finite volume method. The hydrodynamic characteristics, dynamic pressure, turbulent kinetic energy, turbulent viscosity, Nusselt number, skin friction, and the thermal enhancement factor (TEF) are investigated for a range of Reynolds number (Re) from 5000 to 20,000. The obtained results revealed that the TEF values are important (TEF > 1) for all Re values under investigation. The TEF values are between 1.2 and 3.5. An increase in the TEF values was observed with increased Reynolds number, where the maximum value of TEF of about 3.5 was achieved at Re = 20,000. At this value of Re, the normalized heat transfer value (Nu/Nu(0)) is the highest, while the normalized friction values (f/f(0)) are the lowest. This demonstrates the usefulness of the suggested vortex generators combined with the fluid (H-2) for the successful thermal and dynamic performance within the smooth channels.
Keywords: Solar channel collectors; Solar heat exchangers; Forced-convection; Vortex generators; Attached fins and detached bars